PERANAN KEPOLISIAN DALAM MENANGGULANGI TINDAK PIDANA KEJAHATAN ASUSILA YANG DILAKUKAN ORANG DEWASA TERHADAP ANAK DI KOTA PEKANBARU - Harinal Setiawan; Dody Haryono; Mukhlis R (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2014)
Are immoral act or behavior that deviates from the norms or rules of politeness which currently tends to occur among many people, especially teenagers. Islam with the Quran and Sunnah have put up a frame for human life in order to be beautiful and clean life of depravity. According to the Islamic view, high and low spirituality (spiritual) in a society is closely related to all his behavior, not only system behavior besifat mahdah worship (special) such as prayer and fasting, but also the behavior of worship are ghairu mahdah (general) such as the matters related to social. The factors that lead to criminal acts are immoral because of the times and technological advances are issuing new products such as films, videos negative effect that makes a person who saw the movie or the video wants to do what they see in movie or video, presence of books in the negative smell that makes someone want to read delusional and immoral actions, issues of economic pressures, and the lack of understanding of the values of religion and morals. The factors that lead to criminal acts are immoral because of the times and technological advances are issuing new products such as films, videos negative effect that makes a person who saw the movie or the video wants to do what they see in movie or video, presence of books in the negative smell that makes someone want to read delusional and immoral actions, issues of economic pressures, and the lack of understanding of the values of religion and morals. In the case of a criminal act committed immoral adults to children in the city of Pekanbaru is an issue and the need for the role of the police against the immoral criminal offense committed against a child adults in the city of Pekanbaru.